Accounting information: perceptions of European and non-European auditors. (6th March 2020) - Benetti, Cristiane; Reginato, Luciane
Purpose - The main objective of this study was to put in evidence the perceptions of auditors on the disclosure of accounting information across European and non-European countries. Methodology - By means of a survey, we have investigated whether auditors in different countries share the same views on the usefulness and goals of the financial reporting process, using descriptive statistics and bivariate correlation tests to analyse the responses to multiple-choice questions. Findings - There were some differences in the auditors' perceptions on the disclosure of accounting information in different countries or with different demographic characteristics. In general, creditors and institutional investors were the most important stakeholders. Furthermore, auditors believe that managers can disclose mandatory and voluntary information for their own benefits. Originality - This study explains the differences and similarities in the auditors' perceptions on the accounting disclosure from a European and non-European perspective.